Identification of salivary gland proteins depleted after blood feeding in the malaria vector Anopheles campestris-like mosquitoes (Diptera: Culicidae). - Sriwatapron Sor-suwan; Narissara Jariyapan; Sittiruk Roytrakul; Atchara Paemanee; Atchara Phumee; Benjarat Phattanawiboon; Nuchpicha Intakhan; Wetpisit Chanmol; Paul A Bates; Atiporn Saeung; Wej Choochote (PLoS ONE)
Malaria sporozoites must invade the salivary glands of mosquitoes for maturation before transmission to vertebrate hosts. The duration of the sporogonic cycle within the mosquitoes ranges from 10 to 21 days depending on the parasite species and temperature. During blood feeding salivary gland proteins are injected into the vertebrate host, along with malaria sporozoites in the case of an infected mosquito. To identify salivary gland proteins depleted after blood feeding of female Anopheles campestris-like, a potential malaria vector of Plasmodium vivax in Thailand, two-dimensional gel electrophoresis and nano-liquid chromatography-mass spectrometry techniques were used. Results showed that 19 major proteins were significantly depleted in three to four day-old mosquitoes fed on a first blood meal. For the mosquitoes fed the second blood meal on day 14 after the first blood meal, 14 major proteins were significantly decreased in amount. The significantly depleted proteins in both groups included apyrase, 5'-nucleotidase/apyrase, D7, D7-related 1, short form D7r1, gSG6, anti-platelet protein, serine/threonine-protein kinase rio3, putative sil1, cyclophilin A, hypothetical protein Phum_PHUM512530, AGAP007618-PA, and two non-significant hit proteins. To our knowledge, this study presents for the first time the salivary gland proteins that are involved in the second blood feeding on the day corresponding to the transmission period of the sporozoites to new mammalian hosts. This information serves as a basis for future work concerning the possible role of these proteins in the parasite transmission and the physiological processes that occur during the blood feeding.